Preventive effects of Bifidobacterium lactis Probio-M8 on ovalbumin-induced food allergy in mice - Jialu Shi; Yan Xu; Cheng Liu; Shizhi Wang; Jin Wang; Vijaya Raghavan (Food Science and Human Wellness)
Food allergy is a significant public health concern globally. Certain probiotics have been found to enhance food allergy by regulating immune-microbe interactions in animal models and patients. However, the effects of Bifidobacterium lactis Probio-M8 on food allergy have not been thoroughly investigated. The present study examined the anti-allergic properties of Probio-M8, particularly in relation to immune response and gut microbiota composition. Results demonstrate that oral administration of Probio-M8 effectively mitigated the allergy symptoms triggered by ovalbumin (OVA) by ameliorating the morphological damage in the jejunum, reducing OVA-specific IgE and histamine levels in the serum, and suppressing Th2 cytokines (interleukin (IL) 4 and IL-13) while increasing Th1 cytokines (interferon (IFN) γ) and regulatory T (Treg) cytokines (IL-10 and transforming growth factor (TGF) β1) in the culture supernatants of splenic cells. Furthermore, Probio-M8 effectively altered the diversity and composition of gut microbiota, particularly the relative abundances of Akkermansia_muciniphila in OVA-induced mice. Compared to the OVA group, the Probio-M8 group showed a decrease in the relative abundance of Akkermansia_muciniphila. In conclusion, Probio-M8 demonstrates the potential to alleviate food allergy by regulating the Th1/Th2 response and modulating gut microbiota, thereby offering a novel therapeutic strategy for patients with food allergy.